Induction of immune unresponsiveness to concordant islet xenografts by intrahepatic preimmunization and transient immunosuppression. - Goss, J A (1994)
Streptozotocin-induced, diabetic mice (C57BL/6) were preimmunized by injecting 25 low temperature, cultured Wistar-Furth (WF) rat islets into the portal vein, and the recipients received one injection of mouse and rat antilymphocyte sera. 3 wk later, fresh WF islets were transplanted under the kidney capsule of the preimmunized recipients, and normoglycemia was maintained in all 13 recipients for 60 d. Removal of the grafts at 60 d returned the mice to a diabetic state. Transplants of fresh WF islets under the kidney capsule without pretreatment of the recipients had a mean survival time of 16.5 +/- 2.5 d. These findings demonstrate that immune unresponsiveness can be achieved across a concordant, islet xenograft barrier within 3 wk after intrahepatic preimmunization with a small number of donor rat islets and transient immunosuppression with antilymphocyte sera.